Respuesta :
Answer:
D
Step-by-step explanation:
f(x) = x³ (original function)
f(x) = x³ - 6 (shifted 6 units in the negative y direction - i.e 6 units down)
f(x) = (x+4)³ - 6
= [x- (-4) ]³ - 6 (shift 4 units in the negative x direction - i.e 4 units left)
adding up all the transformations, we get
4 units left and 6 units down (which corresponds to D)
A function assigns the value. The correct option is D, g(x) is shifted 4 units to the left and 6 units down.
How does the transformation of a function happen?
The transformation of a function may involve any change.
Usually, these can be shifted horizontally (by transforming inputs) or vertically (by transforming output), stretched (multiplying outputs or inputs) etc.
If the original function is y = f(x), assuming the horizontal axis is the input axis and the vertical is for outputs, then:
Horizontal shift (also called phase shift):
- Left shift by c units, y=f(x+c) (same output, but c units earlier)
- Right shift by c units, y=f(x-c)(same output, but c units late)
Vertical shift
- Up by d units: y = f(x) + d
- Down by d units: y = f(x) - d
Stretching:
- Vertical stretch by a factor k: y = k × f(x)
- Horizontal stretch by a factor k: y = f(x/k)
A function assigns the value of each element of one set to the other specific element of another set.
Given that the parent function is f(x)=x³, while the transformed function is g(x)=(x+4)³ - 6. Therefore, the transformation of the parent function that result in transformed function is that g(x) is shifted 4 units to the left and 6 units down.
Hence, the correct option is D, g(x) is shifted 4 units to the left and 6 units down.
Learn more about Transforming functions here:
https://brainly.com/question/17006186
#SPJ2